Pengaruh Hasil Belajar Keterampilan Menulis Puisi Dengan Model Field Trip Siswa Kelas IV SD Inpres Andi Tonro Kota Makassar - Nurfadillah Y.A.Dewa; Abdul Munir; Abdan Syakur (Politeknik Kampar, 2024)
The main problem in this research is that there is an influence of the field trip model on the learning outcomes of poetry writing skills for fourth grade students at SD Inpres Andi Tonro, Makassar City. This research aims to describe the influence of learning outcomes on poetry writing skills using a field trip model for fourth grade students at SD Inpres Andi Tonro, Makassar City.This type of research is quantitative research that uses experimental research (pre-experimental design) with a one-group pretest-posttest design. The population in this study were all fourth grade students at SD Inpres Andi Tonro, Makassar City with a sample size of 48 students. The research instruments used to collect data were tests (pretest-posttest) and observation sheets.T he data analysis technique used in this research uses descriptive statistical analysis and inferential statistical analysis with the t test. The results of the research prove that there is an influence on the results of learning poetry writing skills using the field trip model for fourth grade students at SD Inpres Andi Tonro, Makassar City.